Early case of breast cancer diagnosed through cancer screening out patient department - Solanki, Nirali; Shah, Anand; Kotadia, Bhanuprasad; Patel, Rohini; Hariyani, Sweta (International Journal Of Community Medicine And Public Health, 2023)
Breast cancer is the most common malignancy among women worldwide. In addition to being the most prevalent, breast cancer also kills more women from cancer than any other type. It has now overtaken lung cancer as the leading cause of cancer incidence globally in 2020, with approximately 2.3 million new cases, accounting for 11.7% of total cancer cases. As per the cancer registry report by NCDIR, In India, the majority of breast cancer cases are identified at an advanced stage. Here, we'd like to talk about a breast cancer case that was diagnosed early in our hospital through the cancer screening out-patient department (OPD) running within the institute.